Classic Light Transmission Platelet Aggregometry: Do We Still Need it? - Gebetsberger, Jennifer; Prüller, Florian (Hämostaseologie, 2023)
For more than 50 years, light transmission aggregometry has been accepted as the gold standard test for diagnosing inherited platelet disorders in platelet-rich plasma, although there are other functional approaches performed in whole blood. In this article, several advantages and disadvantages of this technique over other laboratory approaches are discussed in the view of recent guidelines, and the necessity of functional assays, such as light transmission aggregometry in the era of molecular genetic testing, is highlighted.
Keywords: blood platelet disorders; platelet function tests; platelet aggregation